Investigating factors for increased gonorrhoea re-infection in men who have sex with men attending a genitourinary clinic: a qualitative study. (August 2017) - Payne, L; Lawrence, D; Soni, S; Llewellyn, C; Dean, G
The number of confirmed cases of gonorrhoea increased by one-third in England from 2013 to 2014 and the incidence increased by 32% in men who have sex with men (MSM). In our clinic, annual incidence increased by 28.8% (2013) and re-infection (second infection within one-year of initial infection) rose from 6.7% as a proportion of total infections (2009) to 19.4% (2013). The aim of this study was to explore reasons for repeat gonorrhoea infections among MSM. We interviewed 16 MSM about knowledge and awareness of gonorrhoea, antibiotic resistance and attitudes towards safe sex. We used qualitative methods to investigate the potential causes for the rise in gonorrhoea re-infection. Mobile applications were used to meet casual sex partners and arrange impromptu group-sex parties with partner anonymity making contact tracing difficult. The use of recreational drugs was widespread. It was suggested that new technologies could also be used to increase awareness of STI trends and services for at-risk individuals. Participants were concerned about global antibiotic resistance, but felt that behaviour would not change unless there was local evidence of this. Despite knowing gonorrhoea prevalence was high, participants felt their behaviour was unlikely to change and frequently felt resigned to repeat infections. The use of geosocial networking applications to arrange sexual encounters may be contributing to a rise in STIs, as well as recreational drugs, alcohol and sex parties. Networking applications could increase awareness and advertise testing opportunities. In some cases, risk-taking behaviours are unlikely to change, and for these men, regular sexual health screens should be encouraged to detect and treat infections earlier and reduce onward spread.